Graphene Oxide as An Efficient Photocatalyst For Photocatalytic Reduction of CO2 Into Solar Fuel - Shehzad, N. (Universiti Malaysia Pahang, 2018)
Photocatalytic reduction of CO2 into solar fuel such as methane and methanol, is an attractive approach to simultaneously solve the energy crisis and global warming problem. Herein, comparative photocatalytic activity of graphene oxide nanosheets have been investigated for photocatalytic reduction of CO2 into methane and methanol in continuous gas and liquid phase photoreactor system. The graphene oxide sheets were prepared according to Tour's method. The chemical composition and optical properties was evaluated through XPS and UV-vis spectroscopy. Graphene oxide nanosheets exhibited maximum amount of 224.87 Î¼mol/g.h methanol and 14.8 Î¼mol/g.h methane in liquid and gas phase system, respectively. Higher yield of methanol in liquid phase compared to methane in gaseous system can be attributed to dispersion of graphene oxide sheets in water. Hence, graphene oxide nanosheets are efficient photocatalyst for CO2 reduction into methanol. Nevertheless, further research is essential to improve the photostability of graphene oxide sheets for real application of photocatalytic CO2 reduction. Â© Universiti Malaysia Pahang, Malaysia.